Naming the local : medicine, language, and identity in Korea since the fifteenth century - Suh, Soyoung (Harvard East Asian monographs, 2017)
Examines the role of "locality" in medical innovations in Korea by tracing the origins of five key medical terms. Emerging within specific moments from the fifteenth to the twentieth centuries, each term represents both the aspirations and limitations of registering the local in the existing configuration of Korean medicine.--